Perbandingan Abnormal Return Saham Sebelum Dan Sesudah Perubahan Waktu Perdagangan Selama Pandemi Covid-19 - Randi Fadillah; Muhammad Mansur; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of this research is To find out the difference in the average Abnormal Return of stocks before and after the announcement of the Covid-19 pandemic. The variables used in this study were Abnormal Return and the announcement of the Covid-19 pandemic. The data analysis technique used in this research is the Parametric t-test and the non-parametric t-test. The population and sample in this study are companies listed on the LQ-45 index as a whole. The results state that there is a difference in Abnormal Return between before and at the time of the announcement of the Covid-19 pandemic, that there is a difference in Abnormal Return during and after the announcement of the Covid-19 pandemic and there is a significant difference in Abnormal Return before and after the Covid-19 pandemic. Keywords: Covid-19, Pandemic, Abnormal Return, Capital Market, Stocks, LQ-45 Index, Composite Stock Price Index, Companies, Indonesia Stock Exchange.